Besagood MSME: An Innovative Product Made from Sago as an Alternative to Replace Rice as a Staple Food - Resdati Resdati; Yusmar Yusuf; Rd Siti Sofro Sidiq; Yesi; Rachma Widyana Putri (Journal of Applied Business and Technology, 2026)
This research was conducted to determine the development of sago MSMEs in Indonesia, especially in Meranti. This study used qualitative research methods by interviewing a student at the University of Riau (Muhammad Agung Islamy and Bagus Duhan Irfandy) who has a Sago MSME in Meranti Besagood, Mrs. Praptini is the owner of the Sagu Kite MSME, and Mr. Miftahulaid is the secretary of the Meranti Islands Trade and Industry Department. Besagood has established due to the concerns of Besagood founder Muhammad Agung Islamy and Co-Founder, Bagus Duhan Irfandy, about the price of sago which at that time was not competitive on the market. Since 2020, they have started to innovate to produce products that can be more competitive in the market. This year, Besagood launched two new products, namely SeSaMe (Seblak Sago Meranti), MiGuMek (Sago Mie Nyemek) and SaguNasDuk (Sago Nasi Uduk) which are instant products that are available in Pekanbaru shops such as the airport or other souvenir shops. Besagood products received appreciation from the tourism and creative economy ministry when they attended the tourism and creative economy ministry activities in October at Ciputra Mall.